TRANSFORMASI KIMIA SENYAWA BELERANG, DAMPAK DAN PENANGANANNYA - Sopiah, Nida (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Chemical transformation in the atmosfeer occurs because of antropogenic andantropogenic activity. It can be existing in difference forms and followsbiogeochemical complex cycles. If this chemical transformation of sulfur is over the environmental support ability, there will be serious impacts in many sectors of life, such as environmental pollution, decreasing of healt level, and affecting the agricultural productivity. The effort of preventive and recovery of environment must be done for repairing the polluted environmental to become the conditions which are more friendly with the environment.